UJI AKTIVITAS ANTIDIABETES EKSTRAK ETANOL DAUN BANGUN-BANGUN (Plectranthus amboinicus Lour.) PADA TIKUS PUTIH JANTAN YANG DIINDUKSI ALOKSAN - Zuhairiah Zuhairiah; Yosy Cinthya Eriwaty Silalahi; Ariyanti Ariska (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Bangun-Bangun leaves contain phytochemical compounds such as phenolic compounds and flavonoids which have potential as antioxidant activity. This study aims to determine the antidiabetic activity of the ethanolic extract of Bangun-Bangun leaves on reducing blood glucose levels (KGD) of male white rats by using the glucose tolerance test method and the alloxan induction test. The study was conducted by grouping rats where each group consisted of 5 rats, the fasting KGD was measured. Then, a group I was given Na-CMC 1% BW, group II was given glibenclamide 0.45 mg/kg BW, group III was given EEDBB at a dose of 200 mg/kg BW, group IV was given EEDBB at a dose of 250 mg/kg BW and group V was given EEDBB dose of 300 mg/kg BW. In the glucose tolerance test, each group was given a 50% concentration of glucose solution. Furthermore, measurements of KGD were carried out at 30, 60, 90, and 120 minutes. In alloxan induction, 25 test animals weighing ±150-200 g that had been fasted were divided into 5 groups and then KGD was measured. The rats were then induced with a dose of 150 mg/kg BW of alloxan intraperitoneally. Diabetic rats were then given the test preparation orally for 15 consecutive days. Furthermore, glucose levels were measured on the 3rd, 5th, 7th, 9th, 11th, 13th, and 15th days. The results concluded that EEDBB can reduce blood glucose levels of male white rats induced by alloxan.